Performance evaluation of compound parabolic solar collector using different nanofluids: An experimental study - Farhan, Muhammad; Shahid, Muhammad Ihsan; Jamil, Furqan; Usman, Muhammad; Mujtaba, M. A.; Saleem, Muhammad Wajid; Nasir Shah, Syed; Saghir, Shahid; Yusuf, Abdulfatah Abdu; Mousa, Mohamed; El-Shafay, A.S. (Frontiers in Energy Research, 2022)
The article reports an experimental study on a non-tracking compound parabolic collector (CPC) with nanofluid and hybrid nanofluids (NFs). An experimental setup was fabricated having a concentration ratio of 4.17, 0.828 m2 collector area, 24° of half acceptance angle, and an evacuated tube receiver having 1.85 m length. Fluids like water and NFs have been investigated in CPC performance improvement, but current research deals with NFs and hybrid NFs in a CPC as rare studies are found on a CPC using NFs. The 0.010 and 0.015 wt% concentration were used of nanofluids (NFs) which were silica/water + ethylene glycol (SiO2)/(H2O + EG), and hybrid nanofluids of magnesium oxide + carbon black/water (MgO + CB/H2O) and carbon black + graphene nanoplatelets/water (CB + GNPs/H2O) at flow rates of 0.020, 0.015, and 0.010 kg/s. The experimentation was performed under real climate conditions of Taxila, Pakistan, and solar irradiance and ambient temperature were measured to determine the performance of the CPC in comparison to a simple base fluid which was water. The experimental results revealed that a maximum temperature difference of 8.5°C with an around thermal efficiency of 38.51% was achieved for hybrid pair of MgO + CB at a flow rate of 0.010 kg/s and volumetric concentration of 0.015 wt%. The efficiency variation using NFs (SiO2/EG + H2O) varies from 12.8% to 59.1% from lowest 0.010 kg/s to highest 0.020 kg/s flow rates, and volumetric concentrations (0.010 and 0.015 wt%) of nanoparticles. For similar experimental conditions, efficiency variation for (CB + GNPs) pair varies from 14.2% to 65.6% for aforementioned conditions. Efficiency variation from 15.3% to 66.3% was attained using MgO + CB in the base fluid of water for said flow rates and volumetric concentrations of nanoparticles. In addition, an efficiency enhancement of 24.3%, 30.8%, and 31.5% was observed for SiO2/EG + H2O, CB + GNPs/H2O, and MgO + CB/H2O, respectively, at maximum flow rates and volumetric concentration of nanoparticles as compared to water. Therefore, the usage of hybrid-based NF in the CPC is beneficial in terms of efficiency enhancement, and it will bring young research workers to get deep into this field to bring revolution in the area of solar energy.